Starting out right a guide to promoting children's reading success - Burns, Marie Susan; Griffin, Peg.; Snow, Catherine E.; Committee on the Prevention of Reading Difficulties in Young Children (Washington, D.C. National Academy Press, 1999)
"Presents practical guidelines, program descriptions, advice on resources, and strategies that can be used by parents and caregivers to provide children, from birth through the first years of formal training, with a solid basis upon which to build reading skills."
Introduction -- Growing up to read : birth through age four -- Becoming real readers : kindergarten through grade three -- Preventing reading difficulties.
Keywords: Reading (Early childhood) -- United States; Reading disability -- United States